2018
DOI: 10.1016/j.fertnstert.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, hypertension, and hyperlipidemia in mothers, fathers, sisters, and brothers of women with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: PROSPERO 2016 CRD42016048557.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 78 publications
3
36
0
5
Order By: Relevance
“…This is consistent with previous reports that maternal testosterone exposure increases anxietylike behavior and impacts the limbic system in the offspring (38,39). Previous studies have shown a high incidence of familial aggregation of PCOS (11,12,30,35), which is more likely to occur in first-degree relatives (35). The same findings were confirmed by our experiment.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with previous reports that maternal testosterone exposure increases anxietylike behavior and impacts the limbic system in the offspring (38,39). Previous studies have shown a high incidence of familial aggregation of PCOS (11,12,30,35), which is more likely to occur in first-degree relatives (35). The same findings were confirmed by our experiment.…”
Section: Discussionsupporting
confidence: 94%
“…Due to its familial clustering and peripubertal onset, PCOS is characterized as an autosomal dominant genetic disease (9). Polycystic ovaries, testosterone levels, paternal metabolic syndrome (MBS) and type 2 diabetes mellitus (T2DM)-related defects in insulin secretion and action are all genetic factors for PCOS (4,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic ovary syndrome (PCOS) is a common and complex endocrine condition which affects 8 to 13 per cent of reproductive age women . Women with PCOS present with a range of features including reproductive, metabolic and psychological features .…”
Section: Introductionmentioning
confidence: 99%
“…There is an important communication between granulosa cells and an oocyte in a developing follicle, and gene expression in maturing GCs is closely related to the production of competent oocytes (Cillo et al, 2007;Hamel et al, 2008;Jiang et al, 2010). GCs play a critical role in pathologic folliculogenesis not only in normal folliculogenesis but also in both benign disorders such as polycystic ovary syndrome (Yilmaz et al, 2018), early ovarian failure (POF), also called early ovarian failure. Some authors have found that granulosa cell apoptosis is the primary factor leading to follicular atresia and affects oocyte structure and oocyte development potential (Han et al, 2006;Elmore, 2007;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%